Tahlil ‘Amaliyah Ta’lim al-Lughah al-‘Arabiyah fi al-Madrasah al-Mihiniyah al-Wihdah (SMKIT) Khairul Ummah Rejang Lebong - Eni Widianti; Nur Jannah; Renti Yasmar (IAIN Kediri, 2020)
The purpose of this study is to analyze and describe the process of learning Arabic in SMKIT Khoiru Ummah Rejang Lebong which includes the Arabic learning process, namely : (1). Arabic learning process planning (rpp) Arabic learning, Arabic learning materials, Arabic learning methods, Arabic learning media and Arabic learning evaluation. (2) problems in the process of learning Arabic in SMKIT Khoiru Ummah Tasik Malaya Rejang Lebong. (3) the solution to the problem of learning Arabic in SMKIT Khoiru Ummah Tasik Malaya Rejang Lebong. This type of research is descriptive qualitative. Data collection techniques using interview, observation and documentation. The results of the study are as follows: (1). RPP and Arabic subject syllabus refer to the curriculum of the ministry of religion of the republic of Indonesia. The material taught is not in accordance with the rpp and syllabus that has been prepared. The material is in the form of reading texts, so the material taught does not vary. The method used is the lecture method. The media used are simple media such as blackboards, markers, and paper. The evaluation is in the form of a written test. (2) the problem of learning Arabic first, students are still having difficulty in translating a reading or qiro 'and writing Arabic or dictation imla'. The material in the curriculum is not packaged and arranged properly by the teacher because it is very monotonous only limited to the qiro'ah text. Third, the method used is the lecture method, the method does not vary in the learning process. The media used is only driven by textbooks and stationery such as blackboards, markers and paper Lu'bah lughawiyah has not been implemented. Even so many language games that can be used like children's songs are translated into Arabic. The second problematic is the heterogeneous educational background of students and the lack of motivation of students of SMKIT 45 | تحليل عملية تعليم اللغة العربية في املدرسة املهنية الوحدة خيراألمة ريجانج ليبنج Khoiru ummah Rejang Lebong. Students do not recognize the form of Arabic letters or writing, difficulty in arranging or connecting Arabic letters and difficulties in drawing '. Then less follow-up or reciprocity from the teacher and students on students' Arabic language skills. (3) the solution to the problem of learning Arabic in SMKIT Khoru ummah Rejang Lebong. First about the difficulty of students in translating an Arabic text or text and writing in Arabic, the teacher must use methods that are in accordance with the material presented such as the 'ilma method' and the qiro 'method. in the preparation of the material the teacher must adjust to the level of his education, because each level of education students have different abilities. the media used must vary such as implementing Arabic games with children's songs translated into Arabic. The second problematic students who have different educational backgrounds teachers must vary the methods and media in the delivery of material so that students easily understand the material presented even though they have never learned Arabic. In the introduction of Arabic letters the teacher can use the song and game method. Furthermore, with the lack of reciprocity of teachers and students on Arabic language skills there must be a sense of responsibility of a teacher towards students because one of the requirements for professional teachers is the teacher who is responsible for the ability of students.